Penggunaan Media Big Book untuk Meningkatkan Kemampuan Berpikir Kritis Siswa di Kelas V Sekolah Dasar - Issaura Sherly Pamela; Suci Hayati; Rila Suci Insani (Jurnal Gentala Pendidikan Dasar, 2019)
This study aims to improve students' critical thinking skills by using big book media in class V of SD Negeri 13/1 Rengas Condong in the academic year 2017/2018. This research is a classroom action research (CAR), data taken through observation. This research was conducted in 4 stages, namely Planning, Implementation, Observation, and Reflection. During the process of learning activities using the big book media. The instrument used in this study was in the form of tests and observation sheets, while the benchmarks for the tests were critical thinking indicators, while the benchmarks for observation sheets were critical thinking features using the big book media. The results of this study indicate the use of big book media can improve the critical thinking skills of fifth grade students at SD Negeri 13/1 Rengas Condong. Based on the observation sheet and the test of students' critical thinking skills showed an increase, with the results of the observation sheet percentage of the first cycle of 61.4% with a fairly good category, on the second cycle of 77% with a good category, while the percentage of the results of the first cycle of the test was 45.5 %, in the second cycle increased by 81%. Based on the results of the study, it can be concluded that students' critical thinking skills by using big books in SD Negeri 13/1 Rengas Condong can increase after the use of big book media is applied